Multicomponent dipeptide hydrogels as extracellular matrix-mimetic scaffolds for cell culture applications - Liyanage, Wathsala (Chem Commun (Camb), 2015)
Fmoc-3F-Phe-Arg-NH(2) and Fmoc-3F-Phe-Asp-OH dipeptides undergo coassembly to form two-component nanofibril hydrogels. These hydrogels support the viability and growth of NIH 3T3 fibroblast cells. The supramolecular display of Arg and Asp at the nanofibril surface effectively mimics the integrin-binding RGD peptide of fibronectin, without covalent connection between the Arg and Asp functionality.